Makna Simbol Isi Peras Di Tengah Era Moderenisasi Zaman (Analisis Semiotika Charles Sander Pierce Pada Persyaratan Ritual Masyarakat The Sun Rise Of Java) - Agung Putra Mulyana; Muhammad Irfan (Jurnal Ilmu Komunikasi AKRAB, 2020)
This study describes the of Charles Sanders Pierce’s semiotic analysis simbol peras the contents of the rituals in Banyuwangi. Peras is another name commonly used public offerings Banyuwangi. The aim of this research is to find out the meaning of simbols that exist on the content wring in modernization era banyuwangi society. Juicing is used as a condition of society in implementing hajatnya banyuwangi. The method in this research is descriptive qualitative meaning triangle approach semiotics Charles Sanders Pierce. The results showed that simbols of the contents peras in Banyuwangi is a simbol of hope or values - values that contain the prayer of the owner's intent, not to present to the nation for ghost. In addition to the desired expectations, the form of wringing is also a defense of the traditions of the ancestors.